Impacts of temperature on the mechanical properties of Longmaxi shale outcrops using instrumented nanoindentation. (June 2022) - Espinoza, Wilson F.; Zhang, Fengshou; Dai, Sheng
Abstract: Shale plays an important role in the energy industry and enhanced characterization of the fundamental properties of shale is essential to the economic and safe exploration of this resource. This study investigates the elastic modulus, hardness, and creep behavior of Longmaxi shale outcrops at different temperatures using instrumented nanoindentation. The results show that as the temperature increases from 20 °C to 300 °C, an approximately 10% reduction in measured elastic modulus is observed in the tested samples, whereas the increase in hardness is relatively insignificant, partly because of a relatively high volume fraction of quartz content, i.e., 66.3%. As temperature increases, the tested shale samples undergo brittle to ductile deformation transition as suggested by the number of the pop-in events during indentation loading. The 20-second creep deformation increases by approximately 30% from room temperature to 300 °C and the observed maximum creep deformation is linearly correlated with hardness at all tested temperatures. A smooth surface can render a lower standard deviation in measured elastic modulus and hardness. While a rough surface can lead to an underestimation of hardness, due to the overestimation of the penetration depth as a consequence of surface asperities breakage during indentation. Highlights: Elevated temperature reduces the number of pop-in events during indentation loading of shale, suggesting more ductile deformation. The 20-second creep deformation increases by approximately 30% from room temperature to 300 °C. Elevated temperature reduces the number of pop-in events during indentation loading of shale, suggesting more ductile deformation. The observed maximum creep deformation is linearly correlated with hardness at all tested temperatures. Rough sample surface can lead to an underestimation of indentation hardness.